Combinatorial blockade for cancer immunotherapy: targeting emerging immune checkpoint receptors - Roy, Dia; Gilmour, Cassandra; Patnaik, Sachin; Wang, Li Lily (Frontiers in Immunology, 2023)
The differentiation, survival, and effector function of tumor-specific CD8 + cytotoxic T cells lie at the center of antitumor immunity. Due to the lack of proper costimulation and the abundant immunosuppressive mechanisms, tumor-specific T cells show a lack of persistence and exhausted and dysfunctional phenotypes. Multiple coinhibitory receptors, such as PD-1, CTLA-4, VISTA, TIGIT, TIM-3, and LAG-3, contribute to dysfunctional CTLs and failed antitumor immunity.These coinhibitory receptors are collectively called immune checkpoint receptors (ICRs). Immune checkpoint inhibitors (ICIs) targeting these ICRs have become the cornerstone for cancer immunotherapy as they have established new clinical paradigms for an expanding range of previously untreatable cancers. Given the nonredundant yet convergent molecular pathways mediated by various ICRs, combinatorial immunotherapies are being tested to bring synergistic benefits to patients. In this review, we summarize the mechanisms of several emerging ICRs, including VISTA, TIGIT, TIM-3, and LAG-3, and the preclinical and clinical data supporting combinatorial strategies to improve existing ICI therapies.